Thoracic Spinal Stability and Motion Behavior Are Affected by the Length of Posterior Instrumentation After Vertebral Body Replacement, but Not by the Surgical Approach Type: An in vitro Study With Entire Rib Cage Specimens - Liebsch, Christian; Kocak, Tugrul; Aleinikov, Viktor; Kerimbayev, Talgat; Akshulakov, Serik; Jansen, Jan Ulrich; Vogt, Morten; Wilke, Hans-Joachim (Frontiers in Bioengineering and Biotechnology, 2020)
Spinal tumors and unstable vertebral body fractures usually require surgical treatment including vertebral body replacement. Regarding primary stability, however, the best possible treatment depends on the spinal region. The purpose of this in vitro study was to evaluate the effects of instrumentation length and approach size on thoracic spinal stability including the entire rib cage. Six fresh frozen human thoracic spine specimens with intact rib cages (C7-L1) were loaded with pure moments of 5 Nm in flexion/extension, lateral bending, and axial rotation, while monitoring the relative motions of all spinal segments using optical motion tracking. The specimens were tested (1) in the intact condition, followed by testing after vertebral body replacement at T6 level using a unilateral approach combined with (2) long instrumentation (T4-T8) and (3) short instrumentation (T5-T7) as well as a bilateral approach combined with (4) long and (5) short instrumentation. Significant increases of the range of motion (p < 0.05) were found in the entire thoracic spine (T1-T12) using the bilateral approach and short instrumentation in primary flexion/extension and in secondary axial rotation during primary lateral bending compared to both conditions with long instrumentation, as well as in secondary lateral bending during primary axial rotation compared to unilateral approach and long instrumentation. Compared to the intact condition, the range of motion was significantly decreased using unilateral approach and long instrumentation in flexion extension and secondary lateral bending during primary axial rotation, as well as using bilateral approach and long instrumentation in lateral bending. On the segmental level, the range of motion was significantly increased at T4-T5 level in lateral bending using unilateral approach and short instrumentation and significantly decreased using bilateral approach and long instrumentation compared to their respective previous conditions. Regardless of the approach type, which did not affect thoracic spinal stability in the present study, short instrumentation overall shows sufficient primary stability in the mid-thoracic spine with intact rib cage, while creating considerably more instability compared to long instrumentation, potentially being of importance regarding long-term implant failure. Moreover, short instrumentation could affect adjacent segment disease due to increased motion at the upper segmental level.